Effects of electricity-price policy on electricity demand and manufacturing output. (1st May 2016) - Kwon, Sanguk; Cho, Seong-Hoon; Roberts, Roland K.; Kim, Hyun Jae; Park, Kihyun; Edward Yu, T.
Abstract: The rapid increase of global electricity consumption has led to electric power shortages and economic loss. Price controls for anticipated changes in electricity demand have been widely adopted as a short-term solution. This research analyzes the effects of electricity-price policy on electricity demand and manufacturing output. South Korea's electricity demand in the manufacturing sector is used as a case study. We fail to reject hypotheses that (1) an increase in electricity price decreases electricity demand, which adversely affects manufacturing output and (2) the effects of regionally-varying price changes versus regionally-uniform price changes on electricity demand and manufacturing output differ regionally. Our findings suggest that the South Korean government's plan to increase the electricity price should be implemented with caution. The plan would achieve the objective of mitigating electricity demand to avoid potential power shortages; however, the more rapid increase in electricity prices may trigger a slowdown in the manufacturing sector. Our findings also imply that South Korean experts' suggestion of regionally-varying electricity pricing needs further consideration. Although reflecting regional differences in costs of supplying electricity is important, regionally-varying pricing may prompt a slowdown in the Seoul metro area manufacturing sector where manufacturing is more concentrated than in other areas. Highlights: Analyze input demand for electricity in the manufacturing sector. Compare regionally-varying and regionally-uniform electricity pricing policies. Rapid increases in electricity prices may trigger a slowdown in manufacturing. Regionally-varying pricing may prompt a slowdown in Seoul metro area manufacturing.